Gut Microbiota and Antibiotic Treatments for the Main Non-Oncologic Hepato-Biliary-Pancreatic Disorders - Federica Di Vincenzo; Alberto Nicoletti; Marcantonio Negri; Federica Vitale; Lorenzo Zileri Dal Verme; Antonio Gasbarrini; Francesca Romana Ponziani; Lucia Cerrito (MDPI AG, 2023)
The gut microbiota is a pivotal actor in the maintenance of the balance in the complex interconnections of hepato-biliary-pancreatic system. It has both metabolic and immunologic functions, with an influence on the homeostasis of the whole organism and on the pathogenesis of a wide range of diseases, from non-neoplastic ones to tumorigenesis. The continuous bidirectional metabolic communication between gut and hepato-pancreatic district, through bile ducts and portal vein, leads to a continuous interaction with translocated bacteria and their products. Chronic liver disease and pancreatic disorders can lead to reduced intestinal motility, decreased bile acid synthesis and intestinal immune dysfunction, determining a compositional and functional imbalance in gut microbiota (dysbiosis), with potentially harmful consequences on the host's health. The modulation of the gut microbiota by antibiotics represents a pioneering challenge with striking future therapeutic opportunities, even in non-infectious diseases. In this setting, antibiotics are aimed at harmonizing gut microbial function and, sometimes, composition. A more targeted and specific approach should be the goal to pursue in the future, tailoring the treatment according to the type of microbiota modulation to be achieved and using combined strategies.